3D Window Manager Prototype - Jonsson, Andreas E; Järbratt, Marcus (My University, 2009)
The standard graphical user interfaces on leading operating systems today all use a two dimensional approach for interaction and visualization. Handling several applications using this approach often leads to a cluttered work space which is hard to manage efficiently. Research within the 3D window management area has been performed and many products exist today which utilize 3D in one way or another, but none of these have had any impact on how windows are managed in leading operating systems. The main goal with this thesis was to implement a prototype which utilized 3D in order to manage open windows in a structured way. The result is a system where the user can interact with windows in a 3D world. These windows can be placed and grouped on certain designated areas, which the user is able to navigate between quickly along predefined paths. In order to work with windows they are brought up from the 3D environment to a conventional two dimensional work space. Different users that tried out the prototype encountered no big issues with how the prototype solved navigation and interaction with objects in a 3D environment. While some of them appreciated the product as a whole, some could not see how this would benefit them during their daily computer usage, although they saw advantages with some of the functionality. // Sammanfattning De grafiska användargränssnitt som används i de ledande operativsystemen idag använder ett två-dimensionellt tillvägagångssätt för interaktion och visualisering. Att hantera flera applikationer på detta sätt leder ofta till en rörig arbetsyta som är svår att arbeta med effektivt. Forskning inom fönsterhantering i 3D har utförts och många produkter finns i dagsläget som utnyttjar 3D på ett eller annat sätt, men ingen av dessa har haft något genomslag för hur fönster hanteras i de ledande operativsystemen. Huvudmålet med denna rapport var att implementera en prototyp som utnyttjade 3D för att hantera öppna fönster på ett strukturerat sätt. Resultatet är ett system där användaren kan interagera med fönster i en 3D-värld. Dessa fönster kan placeras och grupperas på särskilda ytor, som användaren snabbt kan navigera mellan längs förbestämda banor. För att arbeta med fönster tas de upp från 3Dmiljön till en konventionell två-dimensionell arbetsyta.En grupp användare som prövade prototypen stötte inte på några större hinder med hur prototypen löste navigering och interaktion med objekt i en 3D-miljö. Medan några av dem uppskattade produkten i sin helhet, hade en del svårt att se hur detta skulle gynna dem i sin dagliga datoranvändning, även om de såg fördelar med delar av funktionaliteten.
Keywords: Datalogi; Övrig informationsteknik; Computer science; Other information technology